High prevalence of obstructive sleep apnea syndrome in Spain's Stroke Belt. Issue 10 (October 2021) - Domínguez-Mayoral, Ana; Sánchez-Gómez, Jesús; Guerrero, Patricia; Ferrer, Marta; Gutiérrez, Carmen; Aguilar, María; Fouz-Rosón, Natalia; Benítez, José María; Pérez-Sánchez, Soledad; Gamero-García, Miguel Ángel; De Torres-Chacón, Reyes; Barragán-Prieto, Ana; et al.
Objective: Spain's so-called Stroke Belt is an area with high prevalence of vascular disease. We aimed to determine the prevalence of undetected obstructive sleep apnea–hypopnea syndrome (OSAHS) among patients with acute ischemic stroke (AIS) in southern Spain. Methods: We conducted a cross-sectional study at the Virgen Macarena University Hospital Stroke Unit during 2018 to 2019. We included patients <72 hours after AIS with a neuroimaging lesion and performed sleep tests. Results: Seventy-two patients were included. The median participant age was 72 years. Mean body mass index was 27.07 kg/m 2, and 40.28% were daily alcohol drinkers. Hypertension, atrial fibrillation, ischemic cardiomyopathy, and previous stroke were detected in 63.9%, 11.1%, 15.3%, and 17.6% of patients, respectively. Polygraphy was feasible in 91.38% of patients. The prevalence of OSAHS was 84.72% (apnea–hypopnea index ≥5). Patients with moderate and severe OSAHS were more likely to be obese and to have a larger neck circumference and facial palsy. The diagnostic criteria of central sleep apnea syndrome were met in only 1.38% of patients. Conclusions: The high prevalence of OSAHS found in the Spanish Stroke Belt justifies further investigation and development of a screening program as a strategy to identify patients with undetected OSAHS.